Effects of 50 Hz magnetic fields on gap junctional intercellular communication in NIH3T3 cells. Issue 4 (3rd April 2015) - Percherancier, Yann; Goudeau, Bertrand; Charlet de Sauvage, Renaud; de Gannes, Florence Poulletier; Haro, Emmanuelle; Hurtier, Annabelle; Sojic, Neso; Lagroye, Isabelle; Arbault, Stéphane; Veyret, Bernard
<x xml:space="preserve">Abstract</x> The present study focused on gap junctional intercellular communication (GJIC) as a target for biological effects of extremely low‐frequency (ELF) magnetic field (MF) exposure. Fluorescence recovery after photobleaching microscopy (FRAP) was used to visualize diffusion of a fluorescent dye between NIH3T3 fibroblasts through gap junctions. The direct effect of 24 h exposure to 50 Hz MF at 0.4 or 1 mT on GJIC function was assessed in one series of experiments. The potential synergism of MF with an inhibitor of GJIC, phorbol ester (TPA), was studied in another series by observing FRAP when NIH3T3 cells were incubated with TPA for 1 h following 24 h exposure to MF. In contrast to other reports of ELF‐MF effects on GJIC, under our experimental conditions we observed neither direct inhibition of GJIC nor synergism with TPA‐induced inhibition from 50 Hz MF exposures. Bioelectromagnetics. 36:287–293, 2015. © 2015 Wiley Periodicals, Inc.